A petroleum additive and preparation method thereof
By using a petroleum additive composed of sodium silicate solution, polypropylene glycol solution, carbon aerogel, microcrystalline cellulose and lubricant, the problem of shale stabilizing agent losing stability under high temperature conditions is solved, and the effective stabilization effect on shale and the maintenance of well wall stability is achieved.
Patent Information
- Application Number
- CN202411251432.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-09-07
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of petrochemical industry, and more specifically, relates to a petroleum additive and a preparation method thereof. Background Art
[0002] In the process of oil extraction, shale stabilizer is an important chemical treatment agent, which is mainly used to suppress the water content in shale, reduce the damage to the well wall stability, and increase the production of shale gas. The mechanism of action of shale stabilizer includes physical action and chemical action.
[0003] The physical effects are mainly reflected in: reducing the pore water pressure of shale, increasing the rock porosity and reducing the storage capacity of pore water by changing the pore structure of shale; inhibiting the activity of water molecules, forming a thin film, hindering the movement of water molecules in the pores of the rock, and reducing the adsorption capacity of water on shale particles; filling the micropores and microcracks of shale, reducing the size of the pores, and hindering the migration of water molecules through the pores and cracks.
[0004] The chemical action is mainly manifested in: the inhibitor reacts with the ions in the shale, changes the charge state in the pores of the shale, and reduces the penetration of water molecules into the shale; changes the hydrophilicity of the rock surface, making the rock hydrophobic, and reducing the adhesion ability of water molecules on the rock surface.
[0005] A common problem faced by commonly used shale stabilizers during use is that they may not be able to completely inhibit the hydration expansion and dispersion of shale, resulting in insufficient wellbore stability. In particular, under high temperature conditions, some shale stabilizers themselves will lose stability, resulting in a further decrease in their stabilizing effect on shale. Summary of the invention
[0006] The technical problem to be solved by the present invention is that during the oil drilling process, the commonly used shale stabilizer often faces the problem of losing its stability under high temperature conditions during use, resulting in the inability to effectively maintain its stabilizing effect on the shale. The present invention provides a petroleum additive and a preparation method thereof.
[0007] The purpose of the present invention is to provide a petroleum additive.
[0008] Another object of the present invention is to provide a method for preparing the petroleum additive.
[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0010] A petroleum additive, comprising the following raw materials in parts by weight:
[0011] 90-100 parts sodium silicate solution
[0012] 40-50 parts polypropylene glycol solution
[0013] 10-12 parts carbon aerogel
[0014] 6-8 parts microcrystalline cellulose
[0015] 2-4 parts lubricant
[0016] Wherein, the mass fraction of the sodium silicate solution is 7-9%;
[0017] The mass fraction of the polypropylene glycol solution is 8-10%.
[0018] First, the above technical solution uses sodium silicate solution as the main shale stabilizer component. This type of inorganic raw material can have a certain stability when facing the high temperature in the oil well; in particular, the sodium silicate solution is easily adsorbed on the surface of the shale, and then forms a protective layer, which reduces the hydration of the shale when it contacts the high-temperature drilling fluid, thereby reducing the expansion and dispersion of the shale under high temperature conditions and enhancing the stability of the well wall;
[0019] Secondly, the inventors found that although the sodium silicate solution can form a protective layer on the surface, it has limited effect on filling the pores of shale. Under high temperature conditions, water can still penetrate into the interior through the pores, resulting in a decrease in the stability of the shale. This problem can be effectively solved by adding polypropylene glycol and carbon aerogel. Specifically, especially under high temperature conditions, polypropylene glycol is easy to form a microemulsion, and its molecules are easy to aggregate to form plastic aggregates. These aggregates can carry carbon aerogels to the pores and cracks of the rock formation under the pressure of the oil well. Under the action of aggregates, carbon aerogels with relatively large particles are more distributed and filled in large pores and cracks, while carbon aerogels with relatively small particles are more distributed and filled in small pores and cracks under the action of aggregates. The hydroxyl groups on the side chains of polypropylene glycol molecules can form a large number of hydrogen bonds with clay molecules in shale, reducing the possibility of dispersion and expansion of shale. In particular, under the action of carbon aerogel, it can ensure that the pores and cracks of the oil well are effectively supported under high temperature and high pressure, so that the mixture formed by polypropylene glycol and clay can be stable.
[0020] Furthermore, the inventors found that by adding a certain amount of microcrystalline cellulose, it can ensure that the product maintains stable performance after being added to the drilling fluid, avoiding phase separation of the components inside the product in the complex environment of the oil well, so that the components of the product can form a synergistic effect on the shale surface, as well as in the pores and cracks.
[0021] Preferably, the fineness modulus of the sodium silicate solution is 2.8-3.2.
[0022] Preferably, the carbon aerogel has a specific surface area of 2300-2500m 2 / g of carbon aerogel; and, the D50 of the carbon aerogel is 2-5 μm, and the sphericity of the carbon aerogel is 8.5-9.0.
[0023] For carbon aerogel, choosing a larger specific surface area can ensure its adsorption capacity, while a smaller particle size is conducive to easier diffusion and penetration into pores and cracks during the above-mentioned diffusion process; in addition, by selecting carbon aerogel with appropriate sphericity, it has a smaller diffusion resistance during the diffusion process, and the powder formed by shale crushing tends to be layered. After being adsorbed by polypropylene glycol, the layered structure and the spherical carbon aerogel are stacked on each other, which is easier to form a dense stack, thereby forming a stronger support for the pores and cracks and maintaining the stability of the shale structure.
[0024] Preferably, the surface of the carbon aerogel is coated with a silane coupling agent;
[0025] The silane coupling agent is selected from any one of silane coupling agent KH-550, silane coupling agent KH-560 and silane coupling agent KH-570.
[0026] Preferably, the limiting degree of polymerization of the microcrystalline cellulose is 80-90.
[0027] For microcrystalline cellulose, if microcrystalline cellulose with a smaller limiting degree of polymerization is selected, the molecular chain is shorter and the hydrogen bonding force formed between molecules is weaker, so it is easier for it to flow and diffuse at high temperature.
[0028] Preferably, the petroleum additive further comprises 10-15% of the mass of the sodium silicate solution in a silicone-acrylic emulsion, and 10-15% of the mass of the sodium silicate solution in a styrene-acrylic emulsion;
[0029] The solid content of the silicone-acrylic emulsion is 44-46%, and the silicone-acrylic emulsion includes silicone-acrylic emulsion particles, and the D50 of the silicone-acrylic emulsion particles is 80-120 nm;
[0030] The solid content of the styrene-acrylic emulsion is 48-50%, and the styrene-acrylic emulsion comprises styrene-acrylic emulsion particles, and the D50 of the styrene-acrylic emulsion particles is 280-300nm.
[0031] The inventors further discovered that by adding a certain amount of silicone-acrylic emulsion and styrene-acrylic emulsion, and the size of the two emulsion particles is at the nanometer level, they can form a protective film on the shale surface together with sodium silicate, and at the same time, they can diffuse into the pores and cracks of the shale. In particular, the emulsion particles of silicone-acrylic emulsion with smaller particle sizes are more likely to diffuse and penetrate internally, and have stronger interactions with the remaining clay in the shale; while the styrene-acrylic emulsion with larger particle sizes, the rigid structure of the benzene ring in its molecular structure can further enhance the strength of the protective film on the shale surface and the structural stability under high temperature conditions.
[0032] Preferably, the lubricant is selected from any one of methyl oleate, fatty acid glyceride, pentaerythritol oleate, sulfonated vegetable oil, dimethyl silicone oil, and methylethoxy silicone oil.
[0033] A method for preparing a petroleum additive, the specific preparation steps comprising:
[0034] Weigh each component according to the raw material composition;
[0035] First, the polypropylene glycol solution, carbon aerogel and microcrystalline cellulose are mixed and poured into a ball mill jar, and ball milled to mix evenly to obtain a ball mill material;
[0036] The obtained ball mill material is mixed with sodium silicate solution and lubricant, stirred and dispersed evenly, and discharged to obtain petroleum additive.
[0037] Preferably, the ball milling and mixing uniformly comprises:
[0038] The total mass of the polypropylene glycol solution, the carbon aerogel and the microcrystalline cellulose is taken as the material mass, and zirconium oxide ball milling beads are added at a material mass to ball milling bead mass ratio of 1:(25-28), wherein the zirconium oxide ball milling beads are ball milling beads with a diameter of 8 mm, ball milling beads with a diameter of 5 mm and ball milling beads with a diameter of 2 mm, which are mixed at a mass ratio of 3:2:1;
[0039] The ball milling mixing was continued for 3-5 hours at a rotation speed of 200-220 r / min and a revolution speed of 120-150 r / min. DETAILED DESCRIPTION
[0040] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0041] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0042] Example 1
[0043] First, the carbon aerogel is dispersed in a 70% ethanol solution by mass, wherein the amount of the carbon aerogel is 10% of the mass of the ethanol solution; the pH is adjusted to 8.0, and then a silane coupling agent of 10% by mass of the carbon aerogel is added, and then the mixture is heated and stirred at a temperature of 65° C. and a stirring speed of 800 r / min for 2 hours, and then filtered, washed and dried to obtain the pretreated carbon aerogel;
[0044] The silane coupling agent is selected from silane coupling agent KH-550;
[0045] The carbon aerogel has a specific surface area of 2300m 2 / g of carbon aerogel; and the D50 of the carbon aerogel is 2 μm, and the sphericity of the carbon aerogel is 8.5;
[0046] Weigh each component according to the raw material composition:
[0047] Take, in parts by weight, 90 parts of sodium silicate solution, 40 parts of polypropylene glycol solution, 10 parts of pretreated carbon aerogel, 6 parts of microcrystalline cellulose, 2 parts of lubricant; and 10% of the mass of the sodium silicate solution by silicone-acrylic emulsion and 10% of the mass of the sodium silicate solution by styrene-acrylic emulsion;
[0048] Wherein, the mass fraction of the sodium silicate solution is 7%;
[0049] The fineness modulus of the sodium silicate solution is 2.8;
[0050] The mass fraction of the polypropylene glycol solution is 8%;
[0051] The limiting degree of polymerization of the microcrystalline cellulose is 80;
[0052] The solid content of the silicone-acrylic emulsion is 44%, and the silicone-acrylic emulsion includes silicone-acrylic emulsion particles, and the D50 of the silicone-acrylic emulsion particles is 80 nm;
[0053] The solid content of the styrene-acrylic emulsion is 48%, and the styrene-acrylic emulsion includes styrene-acrylic emulsion particles, and the D50 of the styrene-acrylic emulsion particles is 280 nm;
[0054] The lubricant is selected from methyl oleate;
[0055] First, the polypropylene glycol solution, carbon aerogel and microcrystalline cellulose are mixed and poured into a ball mill, and the total mass of the polypropylene glycol solution, carbon aerogel and microcrystalline cellulose is taken as the material mass, and zirconium oxide ball milling beads are added according to a material mass and ball milling bead mass ratio of 1:25, wherein the zirconium oxide ball milling beads are ball milling beads with a diameter of 8 mm, ball milling beads with a diameter of 5 mm and ball milling beads with a diameter of 2 mm, which are mixed according to a mass ratio of 3:2:1;
[0056] The ball milling was continued for 3 hours at a rotation speed of 200 r / min and a revolution speed of 120 r / min to obtain a ball milled material;
[0057] The obtained ball mill material, sodium silicate solution and lubricant are mixed, and then the mixture is continuously stirred and dispersed at a speed of 300 r / min for 2 hours by a stirrer, and then the material is discharged to obtain a petroleum additive.
[0058] Example 2
[0059] First, the carbon aerogel is dispersed in an ethanol solution with a mass fraction of 70%, wherein the amount of the carbon aerogel is 11% of the mass of the ethanol solution; the pH is adjusted to 8.0, and then a silane coupling agent with a mass fraction of 10% of the mass of the carbon aerogel is added, and then the mixture is heated and stirred at a temperature of 65° C. and a stirring speed of 800 r / min for 2 hours, and then filtered, washed and dried to obtain the pretreated carbon aerogel;
[0060] The silane coupling agent is selected from silane coupling agent KH-560;
[0061] The carbon aerogel has a specific surface area of 2400 m 2 / g of carbon aerogel; and the D50 of the carbon aerogel is 3 μm, and the sphericity of the carbon aerogel is 8.8;
[0062] Weigh each component according to the raw material composition:
[0063] Take, in parts by weight, 95 parts of sodium silicate solution, 45 parts of polypropylene glycol solution, 11 parts of pretreated carbon aerogel, 7 parts of microcrystalline cellulose, 3 parts of lubricant; and 12% of the mass of the sodium silicate solution by silicone-acrylic emulsion and 12% of the mass of the sodium silicate solution by styrene-acrylic emulsion;
[0064] Wherein, the mass fraction of the sodium silicate solution is 8%;
[0065] The fineness modulus of the sodium silicate solution is 3.0;
[0066] The mass fraction of the polypropylene glycol solution is 9%;
[0067] The limiting degree of polymerization of the microcrystalline cellulose is 85;
[0068] The solid content of the silicone-acrylic emulsion is 45%, and the silicone-acrylic emulsion includes silicone-acrylic emulsion particles, and the D50 of the silicone-acrylic emulsion particles is 100 nm;
[0069] The solid content of the styrene-acrylic emulsion is 49%, and the styrene-acrylic emulsion includes styrene-acrylic emulsion particles, and the D50 of the styrene-acrylic emulsion particles is 290 nm;
[0070] The lubricant is selected from fatty acid glycerides;
[0071] First, the polypropylene glycol solution, carbon aerogel and microcrystalline cellulose are mixed and poured into a ball mill, and the total mass of the polypropylene glycol solution, carbon aerogel and microcrystalline cellulose is taken as the material mass, and zirconium oxide ball milling beads are added according to the material mass and ball milling bead mass ratio of 1:26, wherein the zirconium oxide ball milling beads are ball milling beads with a diameter of 8 mm, ball milling beads with a diameter of 5 mm and ball milling beads with a diameter of 2 mm, which are mixed according to the mass ratio of 3:2:1;
[0072] Under the conditions of a rotation speed of 210 r / min and a revolution speed of 130 r / min, the ball milling mixing is continued for 4 hours to obtain a ball milled material;
[0073] The obtained ball mill material, sodium silicate solution and lubricant are mixed, and then the mixture is continuously stirred and dispersed at a speed of 300 r / min for 2 hours by a stirrer, and then the material is discharged to obtain a petroleum additive.
[0074] Example 3
[0075] First, the carbon aerogel is dispersed in a 70% ethanol solution by mass, wherein the amount of the carbon aerogel is 12% of the mass of the ethanol solution; the pH is adjusted to 8.0, and then a silane coupling agent of 10% by mass of the carbon aerogel is added, and then the mixture is heated and stirred at a temperature of 65° C. and a stirring speed of 800 r / min for 2 hours, and then filtered, washed and dried to obtain the pretreated carbon aerogel;
[0076] The silane coupling agent is selected from silane coupling agent KH-570;
[0077] The carbon aerogel has a specific surface area of 2500m 2 / g of carbon aerogel; and the D50 of the carbon aerogel is 5 μm, and the sphericity of the carbon aerogel is 9.0;
[0078] Weigh each component according to the raw material composition:
[0079] Take, in parts by weight, 100 parts of sodium silicate solution, 50 parts of polypropylene glycol solution, 12 parts of pretreated carbon aerogel, 8 parts of microcrystalline cellulose, 4 parts of lubricant; and 15% of the mass of the sodium silicate solution silicone-acrylic emulsion and 15% of the mass of the sodium silicate solution styrene-acrylic emulsion;
[0080] Wherein, the mass fraction of the sodium silicate solution is 9%;
[0081] The fineness modulus of the sodium silicate solution is 3.2;
[0082] The mass fraction of the polypropylene glycol solution is 10%;
[0083] The limiting degree of polymerization of the microcrystalline cellulose is 90;
[0084] The solid content of the silicone-acrylic emulsion is 46%, and the silicone-acrylic emulsion includes silicone-acrylic emulsion particles, and the D50 of the silicone-acrylic emulsion particles is 120 nm;
[0085] The solid content of the styrene-acrylic emulsion is 50%, and the styrene-acrylic emulsion includes styrene-acrylic emulsion particles, and the D50 of the styrene-acrylic emulsion particles is 300nm;
[0086] The lubricant is selected from pentaerythritol oleate;
[0087] First, the polypropylene glycol solution, carbon aerogel and microcrystalline cellulose are mixed and poured into a ball mill, and the total mass of the polypropylene glycol solution, carbon aerogel and microcrystalline cellulose is taken as the material mass, and zirconium oxide ball milling beads are added according to a material mass and ball milling bead mass ratio of 1:28, wherein the zirconium oxide ball milling beads are ball milling beads with a diameter of 8 mm, ball milling beads with a diameter of 5 mm and ball milling beads with a diameter of 2 mm, which are mixed according to a mass ratio of 3:2:1;
[0088] Under the conditions of a rotation speed of 220 r / min and a revolution speed of 150 r / min, the ball milling mixing is continued for 5 hours to obtain a ball milled material;
[0089] The obtained ball mill material, sodium silicate solution and lubricant are mixed, and then the mixture is continuously stirred and dispersed at a speed of 300 r / min for 2 hours by a stirrer, and then the material is discharged to obtain a petroleum additive.
[0090] Example 4
[0091] Compared with Example 1, this embodiment is different in that:
[0092] No silicone-acrylic emulsion was added, and other conditions remained unchanged.
[0093] Example 5
[0094] Compared with Example 1, this embodiment is different in that:
[0095] No styrene acrylic emulsion was added and other conditions remained unchanged.
[0096] Example 6
[0097] Compared with Example 1, this embodiment is different in that:
[0098] In the silicone-acrylic emulsion, the D50 of the silicone-acrylic emulsion particles is 280nm, and the other conditions remain unchanged.
[0099] Example 7
[0100] Compared with Example 1, this embodiment is different in that:
[0101] In the styrene-acrylic emulsion, the D50 of the styrene-acrylic emulsion particles is 80 nm, and the other conditions remain unchanged.
[0102] Comparative Example 1
[0103] Compared with Example 1, this comparative example has the following differences:
[0104] The carbon aerogel was replaced by activated carbon of equal mass, and the other conditions remained unchanged.
[0105] Comparative Example 2
[0106] Compared with Example 1, this comparative example has the following differences:
[0107] No carbon aerogel was added and the rest of the conditions remained unchanged.
[0108] Comparative Example 3
[0109] Compared with Example 1, this comparative example has the following differences:
[0110] No polypropylene glycol solution was added, and the other conditions remained unchanged.
[0111] The performance tests were performed on the products obtained in the examples and comparative examples. The specific test methods and test results are as follows:
[0112] Linear expansion test:
[0113] The inhibitory effect of the above-mentioned various embodiments or comparative examples on the hydration expansion behavior of sodium bentonite was evaluated by using a linear expansion instrument: 5 g of sodium bentonite was first pressed at 10 MPa for 10 min, then transferred into a linear expansion instrument, and the products obtained in the above-mentioned different embodiments or comparative examples were added respectively, and the sodium bentonite tablets were soaked at room temperature, and the linear expansion rate of each sodium bentonite tablet after 200 min was recorded as 1;
[0114] The inhibitory effect of the above-mentioned various embodiments or comparative examples on the hydration expansion behavior of sodium bentonite under high temperature conditions was evaluated again by using a linear expansion instrument: 5 g of sodium bentonite was first pressed at 10 MPa for 10 min, then transferred into a linear expansion instrument, and the products obtained in the above-mentioned different embodiments or comparative examples were added respectively, and the sodium bentonite tablets were immersed at a temperature of 95° C. After 200 min, the linear expansion rate of each sodium bentonite tablet was recorded.
[0115] The detailed test results are shown in Table 1;
[0116] Table 1: Product performance test results
[0117] Linear expansion rate 1 / % Linear expansion rate 2 / % Example 1 16.8 18.9 Example 2 16.6 18.8 Example 3 16.9 19.1 Example 4 18.5 22.4 Example 5 18.8 24.1 Example 6 18.1 21.8 Example 7 18.3 22.3 Comparative Example 1 25.6 32.1 Comparative Example 2 28.9 38.2 Comparative Example 3 29.5 40.2
[0118] It can be seen from the test results in Table 1 that the product obtained by the present invention has a good inhibitory effect on shale expansion, and its properties on the shale surface can still maintain a long-term inhibitory effect even under high temperature conditions.
[0119] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A petroleum additive, characterized in that: The invention comprises the following raw materials in parts by weight: 90-100 parts of sodium silicate solution; 40-50 parts of polypropylene glycol solution; 10-12 parts of carbon aerogel; 6-8 parts of microcrystalline cellulose; 2-4 parts of lubricant; wherein the mass fraction of the sodium silicate solution is 7-9%; the fineness modulus of the sodium silicate solution is 2.8-3.2, and the carbon aerogel has a specific surface area of 2300-2500m 2 / g of carbon aerogel; and the D50 of the carbon aerogel is 2-5μm, the sphericity of the carbon aerogel is 8.5-9.0, and the surface of the carbon aerogel is coated with a silane coupling agent; the silane coupling agent is selected from any one of silane coupling agent KH-550, silane coupling agent KH-560, and silane coupling agent KH-570; the limiting degree of polymerization of the microcrystalline cellulose is 80-90; wherein the carbon aerogel is a pretreated carbon aerogel, and the carbon aerogel is first dispersed in an ethanol solution with a mass fraction of 70%, wherein the amount of the carbon aerogel is 10% of the mass of the ethanol solution; the pH is adjusted to 8.0, and then 10% of the mass of the carbon aerogel silane coupling agent is added, and then the temperature is 65°C and the stirring speed is 800r / min. After heating and stirring for 2h, it is filtered, washed and dried to obtain the pretreated carbon aerogel; The mass fraction of the polypropylene glycol solution is 8-10%; the petroleum additive also includes 10-15% of the mass of the sodium silicate solution in silicone-acrylic emulsion, and 10-15% of the mass of the sodium silicate solution in styrene-acrylic emulsion; the solid content of the silicone-acrylic emulsion is 44-46%, and the silicone-acrylic emulsion includes silicone-acrylic emulsion particles, and the D50 of the silicone-acrylic emulsion particles is 80-120nm; the solid content of the styrene-acrylic emulsion is 48-50%, and the styrene-acrylic emulsion includes styrene-acrylic emulsion particles, and the D50 of the styrene-acrylic emulsion particles is 280-300nm.
2. The petroleum additive according to claim 1, characterized in that The lubricant is selected from any one of methyl oleate, fatty acid glyceride, pentaerythritol oleate, sulfonated vegetable oil, dimethyl silicone oil, and methylethoxy silicone oil.
Citation Information
Patent Citations
Biology modified silicate drilling fluid system
CN101144009A
Composite natural polymer gel material
CN105837861A